2014
DOI: 10.1038/nmeth.2922
|View full text |Cite
|
Sign up to set email alerts
|

Light-sheet microscopy using an Airy beam

Abstract: Light-sheet microscopy facilitates rapid, high-contrast, volumetric imaging with minimal sample exposure. However, the rapid divergence of a traditional Gaussian light sheet restricts the field of view (FOV) that provides innate subcellular resolution. We show that the Airy beam innately yields high contrast and resolution up to a tenfold larger FOV. In contrast to the Bessel beam, which also provides an increased FOV, the Airy beam's characteristic asymmetric excitation pattern results in all fluorescence con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
555
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 788 publications
(560 citation statements)
references
References 25 publications
2
555
1
2
Order By: Relevance
“…Another benefit of a Bessel beam is that it is essentially non-diffracting, such that an improved Rayleigh range is possible. Bessel beams are by no means the only form of excitation that can improve image quality in the presence of scattering and absorption, with Airy beams also capable of significant improvements in certain circumstances [3].…”
Section: Bessel Beam Illuminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another benefit of a Bessel beam is that it is essentially non-diffracting, such that an improved Rayleigh range is possible. Bessel beams are by no means the only form of excitation that can improve image quality in the presence of scattering and absorption, with Airy beams also capable of significant improvements in certain circumstances [3].…”
Section: Bessel Beam Illuminationmentioning
confidence: 99%
“…When imaging large samples, conventional Gaussian light-sheets are inherently limited by the trade-off between the beam waist and its depth of field, resulting in a non-uniform excitation across the field of view. Lately, Bessel and Airy lightsheets have been proposed because of their larger depth of field and their stability towards on-axis obstructions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this fact other beams have been explored, in particular Bessel beams [55] owing to their longer depth of focus and their 'self-reconstructing' capabilities which suffer less from the effect of scattering [49,50]. Recently, Vettenburg et al [56] have shown that the use of Airy beams may extend the field of view in scanned beam light sheet microscopes up to distances $40-fold greater than the field of view offered by a Gaussian beam and $fourfold that of a Bessel beam.…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…This seemingly counterintuitive discovery was revealed in 2007; a light field with an Airy distribution propagates along a parabolic trajectory [7,8]. This peculiar property makes accelerating beams attractive for a variety of potential applications, such as micromanipulation [9,10], micromachining [11], imaging [12,13], optical routing [14], light bullets [15,16], laser-assisted guiding of electric discharge [17], and plasma generation [18]. Moreover, due to the similar form of wave equations, the fundamental research on optical accelerating beams can be readily generalized to acoustic waves [19], electron waves [20], and plasmonic waves [21][22][23], with a broad and important influence beyond optics.…”
Section: Introductionmentioning
confidence: 99%